Automatic Detection of Subsidence Troughs in SAR Interferograms Using Mathematical Morphology - Maciej Dwornik; Stanisława Porzycka-Strzelczyk; Jacek Strzelczyk; Hubert Malik; Radosław Murdzek; Anna Franczyk; Justyna Bała (Energies, 2021)
In this paper, an automatic algorithm for the detection of subsidence areas in SAR interferograms is proposed. It is based on the analysis of spatial distribution of the interferogram phase, and its coherence and entropy. The developed method was tested for differential interferograms generated on the basis of Sentinel-1 SAR images covering mining areas in South Poland. The obtained results were compared with those achieved using a method based on circular Gabor filters. Performed analysis revealed that the detection rate for the proposed method varied from 34% to 83%. It is an improved method based on Gabor filters that achieved a detection rate from 30% to 53%.